Anti-IL17A in Axial Spondyloarthritis—Where Are We At? - Cheung, Peter P. (Frontiers in Medicine, 2017)
Knowledge regarding the mechanisms of the IL17-IL23 pathway and its role in spondyloarthritis has been pivotal to the development of IL-17 blockade in patients with axial spondyloarthritis. Previously, only anti-TNF has proven to be clinically efficacious in patients with active disease despite non-steroidal anti-inflammatory drugs and physiotherapy. However, up to 50% fail to achieve a clinically significant response. Secukinumab, a fully humanised monoclonal antibody targeting IL-17a has recently been approved for use in patients with active ankylosing spondylitis. Clinical studies and current issues surrounding the use of secukinumab will be discussed.